Technology Readiness and Digital Competing Capabilities: Digital Value Resonance - Panjaitan, Roymon; Moonti, Agustinus; Adam, Echan (Shirkah: Journal of Economics and Business, 2021)
The digital economy for MSMEs still possesses complex problems in the debate over technology readiness and competitive digital capabilities. The increase of dynamic product innovation changes is only effectively supported by digital value resonance. Addressing this issue, this research aims to explore the readiness of technology and the ability to compete digitally for innovative products through the resonance of digital value, especially for multi-business businesses. The data were collected from 170 respondents of small and medium-sized businesses through questionnaires. SEM-PLS techniques were used to analyze the data with a path mediated by digital value resonance on product innovation. The results showed that the resonance of digital value successfully mediated the relationship of technological readiness and digital competing capabilities, as well as direct links to the improvement of innovative products. Digital consumer habits also successfully strengthened the relationship of technological readiness and digital competing capabilities on the resonance of digital value. The advantages of this research lie in the synthesis of proposed digital value resonance variables from the results of resource-based view theory propositions in bridging the previous researcher gaps and contributing as a conceptual novelty model that can personalize digital value in the level of competition and increase MSMEs innovation products.